Development of Nursing Practice Guideline among Spine Surgery Patients in Chonburi Hospital - Saksriwatana, Khwanjit; Ratanamaitrekeart, Rungtip; Anannaweenusorn, Jirathida; Chongjarearn, Angkana (Journal of The Royal Thai Army Nurses, 2020)
This research aimed to develop and study the effects of nursing practice guidelines among spine surgery patients in Chonburi Hospital that applied the concepts of practice development of the National Research Council of Australia. The samples were the perioperative nurses and the spine surgery patients. The data were analized using descriptive statistics and dependent t-test. The results showed that NPG includes three parts; Pre-Operative nursing, Intra-Operative nursing and Post-operative nursing. After following NPG, perioperative nurses have been positively in knowledge and working skills. These changes were significantly higher than before and satisfied in NPG at high level ( x̄ = 4.60, SD =0.18). Spine surgery patients satisfied at highest level ( x̄ = 4.83, SD = 0.21). Complication was not found in spine surgery.